2003
DOI: 10.1073/pnas.0530192100
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoiesis-restricted minor histocompatibility antigens HA-1- or HA-2-specific T cells can induce complete remissions of relapsed leukemia

Abstract: Donor lymphocyte infusion (DLI) into patients with a relapse of their leukemia or multiple myeloma after allogeneic stem cell transplantation (alloSCT) has been shown to be a successful treatment approach. The hematopoiesis-restricted minor histocompatibility antigens (mHAgs) HA-1 or HA-2 expressed on malignant cells of the recipient may serve as target antigens for alloreactive donor T cells. Recently we treated three mHAg HA-1-and͞or HA-2-positive patients with a relapse of their disease after alloSCT with D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
290
1
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 383 publications
(302 citation statements)
references
References 46 publications
5
290
1
5
Order By: Relevance
“…Such T REG may impair HA-1 or HA-2 T CTL -driven graft-versus-leukemia reactions. 34,35 Evidently, the presence of these T REG must also be considered when HA-1-or HA-2-specific T CTL are generated from unselected PBMCs or CD8-enriched populations for the purpose of cellular adoptive immunotherapy. 36 Given our current observations that nonfunctional CD8 ϩ T cells, ie, failure to lyse or produce interferon-␥ when stimulated with minor H alloantigen, can also be expanded from some of our donors (&2, &3, and (2, data not shown), we speculate that naturally established tolerance to minor H antigens may be the result of either the presence of minor H antigen-specific T REG and/or the induction of T-cell anergy.…”
Section: Discussionmentioning
confidence: 99%
“…Such T REG may impair HA-1 or HA-2 T CTL -driven graft-versus-leukemia reactions. 34,35 Evidently, the presence of these T REG must also be considered when HA-1-or HA-2-specific T CTL are generated from unselected PBMCs or CD8-enriched populations for the purpose of cellular adoptive immunotherapy. 36 Given our current observations that nonfunctional CD8 ϩ T cells, ie, failure to lyse or produce interferon-␥ when stimulated with minor H alloantigen, can also be expanded from some of our donors (&2, &3, and (2, data not shown), we speculate that naturally established tolerance to minor H antigens may be the result of either the presence of minor H antigen-specific T REG and/or the induction of T-cell anergy.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Moreover, cytotoxic T lymphocytes (CTLs) directed against these mHags do not cause graft-versus-host disease in an ex vivo skin explant model, 7 and coincide with complete remission of relapsed leukemia and multiple myeloma after HLA-matched HA-1-or HA-2-mismatched donor lymphocyte infusions. 8 HA-1-and HA-2-specific CTLs can be generated in vitro using peptide-pulsed or mHag-transduced autologous dendritic cells (DCs) as antigen-presenting cells (APCs). 9,10 However, expansion of CTLs is difficult due to the limited availability of donor-derived DCs.…”
Section: Introductionmentioning
confidence: 99%
“…DISCUSSION mHA are considered to have a dominant role in mediating graftversus-tumor reactivity after HLA-identical allo-SCT for hematological malignancies. 15,16,17 Recently, we demonstrated that partial T-cell-depleted allogeneic RIC --SCT creates a platform for inducing graft-versus-tumor immunity by post-transplant immunotherapy in patients suffering from MM. Escalating dose DLI could be given to most patients (63%) and vaccination with KLH-loaded recipient DCs was explored in six patients.…”
Section: Case Descriptionmentioning
confidence: 99%